1988
DOI: 10.1227/00006123-198803000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Low Power CO2 Laser-assisted Microvascular Anastomosis: An Experimental Study

Abstract: Low power CO2 laser-assisted microvascular anastomosis (LAMA) was used for saphenous artery autotransplantation in 40 rabbits. Eighty end-to-end anastomoses were performed by three methods (conventional interrupted suture, stay suture + laser, laser without stay suture). The long term patency rate in the three types of anastomosis is 93%, 93%, and 100%, respectively. The time needed for the laser procedure is half to one-third of that required for the interrupted suture method. The tensile strength of the bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Despite numerous studies on the feasibility of using laser welding for microvessel repair, and even some reports of clinical trials with satisfactory results, 18 microsuturing is still used as the standard technique in clinical practice and experimental research. 2,4,5,8,11,12 This study confirms earlier results showing that CO 2 laser welding, with the assistance of an intraluminally placed dissolvable stent, is at least comparable to the more conventional microsuturing method. 5,12 However, this technique has the additional advantages of offering a less timeconsuming but still very reliable and safe procedure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite numerous studies on the feasibility of using laser welding for microvessel repair, and even some reports of clinical trials with satisfactory results, 18 microsuturing is still used as the standard technique in clinical practice and experimental research. 2,4,5,8,11,12 This study confirms earlier results showing that CO 2 laser welding, with the assistance of an intraluminally placed dissolvable stent, is at least comparable to the more conventional microsuturing method. 5,12 However, this technique has the additional advantages of offering a less timeconsuming but still very reliable and safe procedure.…”
Section: Discussionsupporting
confidence: 83%
“…The introduction of laser has potentially made small vessel repair much simpler and eliminates the need for timeconsuming manual suturing. 5,10,11 However, when employed alone, this technique presents some limitations, including the possibility of stenosis at the irradiated sites and the chance of welding the anterior and posterior walls together. 2,5,12 This study has combined the "stented suturing" and "la-ser welding" methods to obtain a hybrid technique, the stented welding technique, utilizing their individual advantages while avoiding their shortcomings.…”
mentioning
confidence: 99%
“…However, in most LAVA studies, stay sutures were still employed to support vessel approximation and anastomotic strength ( Figure 4) [2,7,[12][13][14][15][21][22][23]27,31,34,35,38,42,43,46,47,[68][69][70][71]81]. Several studies in which stay sutures were entirely omitted and the vessel segments were adjoined using microforceps, a balloon catheter, or a polyvinyl alcohol splint reported lower patency rates and were not applicable to all vessel sizes [16,17,23].…”
Section: Summary Of Experimental Resultsmentioning
confidence: 99%
“…Although many studies have reported a normal healing process following full-thickness thermal damage, thermal damage extending beyond the internal elastic lamina is associated with complications such as intimal hyperplasia, thrombosis, and aneurysm formation [13,15,21,34,38,71,72]. Partial thermal damage, limited to the adventitia and upper medial layer, is therefore considered the therapeutic goal.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation